Cinnamic Aldehyde Inhibits Lipopolysaccharide-Induced Chondrocyte Inflammation and Reduces Cartilage Degeneration by Blocking the Nuclear Factor-Kappa B Signaling Pathway - Pu Chen; Anmin Ruan; Jun Zhou; Liuwei Huang; Xiaozhe Zhang; Yufeng Ma; QingFu Wang (Frontiers Media S.A., 2020)
Osteoarthritis (OA), as one of the top 10 causes of physical disability, is characterized by inflammation of the synovial membrane and progressive destruction of the articular cartilage. Cinnamic aldehyde (CA), an α,β-unsaturated aldehyde extracted from the traditional Chinese herbal medicine cinnamon (Cinnamomum verum J.Presl), has been reported to have anti-inflammatory, antioxidant, and anticancer properties. However, the anti-inflammatory effect of CA on OA remains unclear. The purpose of the present study was to investigate the effects of CA on inflammation, and cartilage degeneration in OA. A CCK-8 assay was performed to assess the potential toxicity of CA on cultured human OA chondrocytes. Following treatment with lipopolysaccharide (LPS) and CA, the expression of proinflammatory cytokines, including interleukin (IL)-1β, IL-6, and tumor necrosis factor-alfa (TNF-α), was evaluated using quantitative real-time polymerase chain reaction (RT-qPCR) analysis, enzyme-linked immunosorbent assay, and Western blotting (WB). The production of matrix metalloproteinase-13 (MMP-13) and a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS-5) was also examined using RT-qPCR and WB. Furthermore, to investigate the potential anti-inflammatory mechanism of CA, biomarkers of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) pathway (p65, IKB-α) were detected using WB. The results demonstrated that CA significantly inhibited the expressions of IL-1β, IL-6, TNF-α, MMP-13, and ADAMTS-5 in LPS-induced OA chondrocytes. CA dramatically suppressed LPS-stimulated NF-κB activation. Collectively, these results suggest that CA treatment may effectively prevent OA.